The Dead Sea scrolls : texts and context - Hempel, Charlotte. (Studies on the Texts of the Desert of Judah, 2010)
This volume presents the proceedings of an international conference of the same title held at the University of Birmingham in 2007. The contributors are drawn from the ranks of leading international specialists in the field writing alongside promising younger scholars. The volume includes studies on the contribution of the Scrolls to Second Temple Jewish history, the archaeological context, the role of the temple and its priesthood, as well as treatments on selected texts and issues. These proceedings offer a timely and up to date assessment of the Dead Sea Scrolls and the material remains unearthed at Qumran in their wider context and not infrequently challenge prevailing lines of interpretation. Helen Jacobus has won the Sean Dever Memorial Prize with her contribution to this volume. Commenting on the Dever prize, Professor Carol Meyers of Duke University, North Carolina, said: "The judges thought highly of Helen's meticulous scholarship and careful presentation of the data in her discussion of the zodiac and its role in Jewish calendars."